2020
DOI: 10.1177/0309324720975284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid estimation of fatigue limit for C45 steel by thermography and digital image correlation

Abstract: Combining thermography and Digital Image Correlation (DIC) measurements, this paper aims to experimentally capture the fatigue damage phenomenon in steels, with a methodology allowing to rapidly estimate the fatigue limit. Surface temperatures and displacement fields are collected during fatigue tests performed with blocks of progressively increased stress amplitude, at different stress ratios. Results show that both thermography and DIC-based parameters have bilinear trends as a function of the stress amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 47 publications
6
23
0
Order By: Relevance
“…It is also observed that T o is not subject to steep increases, at least of the order of magnitude reported in other works [2,4,18], where the same material is tested. The absence of an abrupt increase of the curve is likely to be attributed to the lower loading frequencies of the higher stress amplitudes applied in this work (see tables 3, 4).…”
Section: Stepwise Plots: T O 380supporting
confidence: 80%
See 3 more Smart Citations
“…It is also observed that T o is not subject to steep increases, at least of the order of magnitude reported in other works [2,4,18], where the same material is tested. The absence of an abrupt increase of the curve is likely to be attributed to the lower loading frequencies of the higher stress amplitudes applied in this work (see tables 3, 4).…”
Section: Stepwise Plots: T O 380supporting
confidence: 80%
“…This is confirmed by the stabilised hysteresis loops acquired at different σ a and shown in Fig. 17, which also show a significantly smaller area and exhibit a marked ratcheting [2]. The average value of Φ E over the ROI is first considered and subtracted to the phase of the load FH signal (see also eq (15).…”
Section: Stepwise Plots: Ementioning
confidence: 56%
See 2 more Smart Citations
“…Ratcheting: In this stage, some plastic strains in each cycle are added to the structure that is subjected to loading. 3,4…”
Section: Introductionmentioning
confidence: 99%